Study of mindset among learners and educators in an Indian medical school-A questionnaire-based survey - Sujatha Rajaragupathy; Sumitra Govindarajan; Deepika Ponnusamy (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Mindset varies along a spectrum of two extremes- fixed and growth. Individuals with growth mindset embrace new challenges readily and believe that intelligence is malleable. Mindset theory has gained focus as a principal underpinning value of health professions education, as it is aligned with the goals of competency-based education. The study aims to assess the mindset of health professional educators and learners. MATERIALS AND METHODS: A cross-sectional questionnaire-based survey was conducted in a private medical college in South India. A pre-validated modified version of Dweck's (2000) Implicit Theories of Intelligence Questionnaire was administered to the study participants. Participants responded to 10 items using a four-point Likert scale, rating the degree to which they agreed or disagreed with each statement. The quantitative data were expressed in means and percentages. RESULTS: A total of192 students and 25 faculty participated in the study. Among students, 45.8% (n = 88) had strong growth mindset, 42.1% (n = 81) had growth mindset with some fixed ideas, 10.9% (n = 21) had fixed mindset with some growth ideas, and 1% (n = 2) had strong fixed mindset. Among faculty 4% (n = 1) had fixed mindset with growth ideas, 44% (n = 11) had growth mindset with fixed ideas, and 52% (n = 13) had strong growth mindset. DISCUSSION: In this study, educators and learners of a medical school were found to have predominantly growth mindset. Fostering growth mindset among stakeholders of health professions education is essential for effective teaching and learning in competency-based education.